Geographies of Muslim women : gender, religion, and space - Falah, Ghazi-Walid.; Nagel, Caroline Rose. (New York : The Guilford Press, 2005)
This volume explores how Islamic discourse and practice intersect with gender relations and broader political and economic processes to shape women's geographies in a variety of regional contexts.
1. Growing up in Gilgit: exploring the nature of girlhood in northern Pakistan / Sarah J. Halverson -- 2. (Re)Defining public spaces through developmental education for Afghan women / Naheed Gina Aaftaab -- 3. A space of her own: women, work, and desire in an Afghan nomad community / Diana K. Davis -- 4. Changing identities and changing spaces in village landscapes of settled pastoralists in eastern Morocco/ Susanne H. Steinmann -- 5. Transnational Islam: Indonesian migrant domestic workers in Saudi Arabia / Rachel Silvey -- 6. Moral geographies and women's freedom: rethinking freedom discourse in the Moroccan context / Amy Freeman -- Negotiating spaces of the home, the education system and the labor market: the case of young, working-class, British-Pakistani Muslim women / Robina Mohammad -- Islamism, democracy and the political production of the headscarf issue in Turkey / Anna Secor -- Social transformation and Islamic reinterpretation in northern Somalia: the women's mosque in Gabiley / Abdi Ismail Samatar -- Gendered space in the Lebanese women tobacco workers' strike of 1970 / Malek Abisaab -- Writing place and gender in novels by Tunisian women writers / Leila Ayari and Marc Brosseau -- The visual representation of Muslim/Arab women in the daily newspapers in the United States / Ghazi-Walid Falah.
1. Growing up in Gilgit: exploring the nature of girlhood in northern Pakistan / Sarah J. Halverson -- 2. (Re)Defining public spaces through developmental education for Afghan women / Naheed Gina Aaftaab -- 3. A space of her own: women, work, and desire in an Afghan nomad community / Diana K. Davis -- 4. Changing identities and changing spaces in village landscapes of settled pastoralists in eastern Morocco/ Susanne H. Steinmann -- 5. Transnational Islam: Indonesian migrant domestic workers in Saudi Arabia / Rachel Silvey -- 6. Moral geographies and women's freedom: rethinking freedom discourse in the Moroccan context / Amy Freeman -- Negotiating spaces of the home, the education system and the labor market: the case of young, working-class, British-Pakistani Muslim women / Robina Mohammad -- Islamism, democracy and the political production of the headscarf issue in Turkey / Anna Secor -- Social transformation and Islamic reinterpretation in northern Somalia: the women's mosque in Gabiley / Abdi Ismail Samatar -- Gendered space in the Lebanese women tobacco workers' strike of 1970 / Malek Abisaab -- Writing place and gender in novels by Tunisian women writers / Leila Ayari and Marc Brosseau -- The visual representation of Muslim/Arab women in the daily newspapers in the United States / Ghazi-Walid Falah.
Includes bibliographical referances and index.
AAL
Trim Education
Keywords: Muslim women; Women -- Legal status, laws, etc. -- Islamic countries; Human geography